A Effect of Lemongrass Extract Dosage on Airborne Germ Reduction in Dormitory Rooms - Eko Nur Astuti, Sisilia; Sudaryanto, Sigid; Yamtana, Yamtana (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
Air problems are problems that require special attention in human welfare and health. This condition can cause various risks of disease due to poor air quality. Observation results show that the condition of the men's bedrooms in the dormitory is very dirty, students rarely clean their rooms and some students smoke in the room. Initial test results showed that the room humidity was 73%, the room temperature was 31ᵒC and the air germ count was 1.500 colonies/m3. These various factors can influence the number of air germs, so the room needs to be disinfected. One natural ingredient that can be used as a disinfectant is lemongrass stems, because they contain flavonoids such as quercetin, alkaloids, saponins, tannins and polyphenols. The aim of this research was to determine the most effective dose of kitchen lemongrass extract as a natural disinfectant in reducing the number of room air germs. This type of research is Quasi Experimental with a Non Equivalent pretest-posttest Group approach. First, the room is checked for air germ numbers before (pre), then intervention is carried out with kitchen lemongrass extract disinfectant liquid and waited for 1 hour, and finally the air germ numbers are checked after (post). Based on the research results, it can be concluded that among the three disinfectant doses of kitchen lemongrass extract. The 5% dose is the most effective dose in reducing the number of airborne germs with a reduction percentage of 1.033.3 colonies/m3 (65.40%) and meets quality standards.